Varying amounts of scabby wheat added to growing-finishing rations - Koch, B.A.; Pollmann, D.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Scabby wheat, infected with the fungus, Fusarium graminearum and grading No.4, replaced varying percentages of grain in a typical sorghum grain-soybean meal growing-finishing ration. Four pigs eating the control ration made an average daily gain of 1.91 pounds per day and a feed efficiency of 3.44. When 25% of the sorghum grain was replaced by scabby wheat, average daily gain dropped to 1.71 pounds per day and feed efficiency was 3.29. Replacing 50% of the sorghum grain with scabby wheat reduced average daily gain to 1.56 pounds with a feed efficiency of 2.99. Higher percentages of scabby wheat reduced feed intake drastically. The 25% scabby wheat ration contained 0.75 ppm of vomitoxin and the 50% ration contained 2.07 ppm (ration analysis values). All pigs eating rations containing scabby wheat appeared to drink excessive amounts of water.
Keywords: Swine; Scabby wheat; Growing-finishing pigs; Rations